2009
DOI: 10.4028/www.scientific.net/msf.615-617.885
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Carbide UV Based Photovoltaic for Hostile Environments

Abstract: The development of silicon carbide technologies has allowed for the development of sensors and electronics to measure the changes in a variety of hostile environments. A problem has been identified with reliable and efficient ways to power such sensors in these hostile environments. It is likely to be impractical to run power cables to these sensors and battery power has a finite lifetime. Recent research has demonstrated many energy scavenging techniques but to date none have been developed with a view of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Previous reports provide some useful insight into the effects of surface passivation of mainly 3C-SiC (ß-SiC) [3][4][5] where the optical gap can be engineered as a function of size and surface composition. The present study is mainly focussed on addressing the issue for arguably the most technologically relevant SiC 4H-polytype [6,7], by terminating the surface atoms of 4H-SiC QDs with various functional groups that are promising in terms of tuning the optical properties and improving the ambient chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports provide some useful insight into the effects of surface passivation of mainly 3C-SiC (ß-SiC) [3][4][5] where the optical gap can be engineered as a function of size and surface composition. The present study is mainly focussed on addressing the issue for arguably the most technologically relevant SiC 4H-polytype [6,7], by terminating the surface atoms of 4H-SiC QDs with various functional groups that are promising in terms of tuning the optical properties and improving the ambient chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Given this, there is a clear need, and desire, to develop resilient energy harvesting technologies that can support and power electronics deployed in these resilient environments. Previous work has shown silicon carbide UV photovoltaics to be effective energy harvesters at elevated temperatures [5,6] however they have so far only considered for short term temperature elevation. It has been shown that silicon carbide can survive at 400 °C for extended periods [7] and remain electrical and mechanically operational, however what has not been conducted is a study into the long term resilience of the device metalisation and overall long term temperature effects on devices such as these.…”
Section: Introductionmentioning
confidence: 99%